Applying rhetorical analysis to processing technical documents (2019)
Rhetorical discourse analysis (RDA) emphasizes the communicative purpose and organization structures of texts. This paper proposes a rhetorical organization model for business-based technical documents. Using RDA and genre analysis, we define such a model based on functional and structural features in terms of macro-moves, moves, and functions that comprise a type of document called standard operating procedure (SOP). An SOP is a technical document that describes procedures for segments of business processes or policies to be implemented inside organizations (commonly called a procedure manual). We propose a functional-structural framework for analyzing SOP discourses by influencing and restricting their content based on the style of the 'manual' genre. We identify an SOP as a document with procedural information that serves as a relevant source for extracting domain knowledge and business information. We apply this model as an analytical-conceptual procedure for mapping business documents and generating a controlled language output. © 2019 Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.